Effects of hydroethanolic opuntia ficus-indica cladode extract on high-fructose highfat diet-fed growing spraguedawley rats - Zulu, Abigail Zamazulu (My University, 2020)
The consumption of diets rich in refined sugars and fats and lack of exercise are the main contributors to the global increase in the prevalence of obesity, metabolic syndrome (MetS), non-alcoholic fatty liver disease (NAFLD) and type-II-diabetes mellitus (T-II-DM). Opuntia ficus-indica cladode extract possesses antioxidant, anti-inflammatory, anti-obesogenic and antidiabetic properties. This study sought to determine the potential prophylactic effects of the hydroethanolic Opuntia ficus-indica cladode extract against high-fructose high-fat dietinduced metabolic derangements in growing rats modelling children fed obesogenic diets. Ninety-eight 21-day-old weaned Sprague-Dawley rat pups (49 males; 49 females) were randomly allocated to one of five dietary groups and administered the following treatment regimens daily for 12 weeks: group I - standard rat chow (SRC) plain drinking water (PW) + plain gelatine cube (PC); group II - SRC + 2% (w/w) beef tallow (SRCB) + 25% (w/v) fructose solution (FS) + PC; group III- SRCB + FS + 100 mg/kg body mass fenofibrate in gelatine cube (FeC); group IV - SRCB + FS + low dose (50 mg/kg body mass) of Opuntia ficus-indica cladode extract in gelatine cubes (LOpC); group V - SRCB +FS + high dose (500 mg/kg body mass) of Opuntia ficus-indica cladode extract in gelatine cube (HOpC). After the 12-week feeding trial, the rats were subjected to oral glucose tolerance tests following an overnight fast. Immediately thereafter the rats were returned to their respective treatments, allowed a 48-hour recovery period following which they were fasted overnight, and their terminal body masses and fasting blood glucose concentrations were determined prior to euthanasia. Harvested plasma was used in the determination of triglycerides, total and HDLcholesterol, insulin, TBARS and surrogate markers of liver and kidney function. Viscera macromorphometry, liver lipid content and histology were also determined. The high-fructose high-fat diet caused (p < 0.05) increased liver lipid accretion in the rats but increased kidney mass in male rats only. Remarkably, the orally administered hydroethanolic Opuntia ficus-indica cladode extract and fenofibrate prevented the development of the highfructose high-fat diet-induced fatty-liver disease in the male and female rats. Fenofibrate caused (p < 0.05) hepatomegaly, hyperglycaemia and increased (p < 0.05) plasma ALP activity in high-fructose high-fat diet-fed rats. Oral administered of high and low dose of hydroethanolic Opuntia ficus-indica cladode extract protects growing rats against the development of high-fructose high-fat diet-induced fatty-liver disease without compromising liver and kidney function.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2020